Predictors of transient congenital primary hypothyroidism: data from the German registry for congenital hypothyroidism (AQUAPE “HypoDok”) - Matejek, Nicola; Tittel, Sascha R.; Haberland, Holger; Rohrer, Tilman; Busemann, Eva-Maria; Jorch, Norbert; Schwab, Karl-Otfried; Wölfle, Joachim; Holl, Reinhard W.; Bettendorf, Markus (European Journal of Pediatrics, 2021)
Neonatal screening for congenital primary hypothyroidism (CH) may not distinguish between transient (TCH) and permanent dysfunction (PCH), causing potential overtreatment and concerns in affected families. To specify the indication for interruption of therapy, we analysed the German registry “HypoDok” for infants with CH, which oversees 1625 patients from 49 participating centres in Germany and Austria from 1997 until today. A total of 357 patients with a thyroid gland in loco typico were identified and retrospectively grouped according to cessation (TCH, n = 24) or continuation (PCH, n = 333) of l-thyroxine (l-T4) treatment at 2 years of age. The receiver operating characteristic (ROC) analysis was performed to identify cutoffs predicting TCH by screening TSH concentrations and l-T4 dosages. Gestational ages, birth weights and prevalence of associated malformations were comparable in both groups. The cutoff screening TSH concentration was 73 mU/L. The cutoff daily l-T4 dosage at 1 year was 3.1 μg/kg (90% sensitivity, 63% specificity; 36 μg/day) and at 2 years of age 2.95 μg/kg (91% sensitivity, 59% specificity; 40 μg/day). At 2 years of age, specificity (71%) increased when both of these parameters were considered together. Conclusion: The decision to continue or cease l-T4 treatment at 2 years of age in CH patients diagnosed in neonatal screening may be based on their screening TSH concentrations and individual l-T4 dosages at 1 and 2 years of age. Thus, TCH and PCH may be distinguished; overtreatment avoided; and affected families reassured.What is Known:• The course of congenital primary hypothyroidism may be transient, causing potential overtreatment.• The dose ofl-thyroxine at 1 or 2 years of age may predict a transient course of primary congenital hypothyroidism.What is New:• TSH screening concentration andl-thyroxine dosages at 1 and 2 years of age represent reliable predictors for transient congenital primary hypothyroidism with higher sensitivity and specificity when considered together in order to select eligible patients who qualify for treatment withdrawal.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Congenital primary hypothyroidism; Permanent congenital primary hypothyroidism; Prediction; Transient congenital primary hypothyroidism